Sacral chordoma with metastatic dissemination in a child: case report - Camile Cremonese Gobbo; André Bedin; Samir Cezimbra dos Santos; Gabriel Frizon Greggianin; Eduardo Cambruzzi; Jorge Wladimir Junqueira Bizzi (Brazilian Society for Pediatric Neurosurgery, 2022)
Introduction: Chordoma is a rare pathology in the pediatric age group, especially when located in the sacral region. Despite the local infiltrative character, some cases of metastasis are reported. The prognosis of these patients depends on early diagnosis and tumor resection. Case Report: 13 y-o girl transferred with a huge mass lesion in the lumbosacral area. In the primary hospital,she was submitted to a biopsy, whose anatomopathological report showed chordoma. The patient started with pain in the lumbosacral region a year ago, which rapidly evolved to a significant bulging in the area, pain in the posterior region of the left lower limb, urinary retention, and difficulty in walking. A surgical approach, both anterior and posterior, was performed en block resection of the tumor. During the procedures, there was evidence of metastatic dissemination to the ovary and peritoneum. The pathological examination confirmed the initial diagnosis. Due to the late recognition of the condition and the fast evolution of the disease, there was not enough time to perform adjuvant radiotherapy and the patient died. Discussion:  From notochordal remnants, chordoma manifests in less than 5% of patients in the first two decades of life and is occasionally found in the sacral region, but rarely with metastatic dissemination at presentation. These patients open up with the manifestation of local pain and, when not diagnosed early, progress with bulging of the sacral region and tumor dissemination. Management is based on primary resection, for the complete removal of the lesion, followed by radiation therapy.